Digital Smile Design: Patient Satisfaction and Long-Term Outcomes of a Novel Approach to Esthetic Dentistry in Jakarta, Indonesia - Aprilia Sari; Vita Amanda; Daphne Marshall; Fachrudin Sani (Crown: Journal of Dentistry and Health Research, 2023)
Introduction: Digital smile design (DSD) is revolutionizing esthetic dentistry by offering a patient-centric approach to treatment planning and execution. This study aimed to evaluate patient satisfaction and long-term outcomes of DSD in a cohort of patients in Jakarta, Indonesia. Methods: A retrospective study was conducted on 75 patients who underwent DSD-guided esthetic treatments between 2020 and 2023 at a private dental clinic in Jakarta. Patient satisfaction was assessed using a validated questionnaire, and long-term outcomes (functionality, stability, and esthetics) were evaluated through clinical examinations and photographic records at 6, 12, and 24 months post-treatment. Results: High levels of patient satisfaction were reported across all treatment aspects, including communication, predictability, and esthetic outcomes. The majority of patients (92%) expressed satisfaction with their smiles' appearance, and 88% reported improved self-confidence. Clinical evaluations demonstrated excellent long-term stability and functionality of the restorations. Minor complications, such as chipping of veneer material, were observed in 5% of patients. Conclusion: DSD significantly enhances patient satisfaction and achieves predictable long-term outcomes in esthetic dentistry. This technology empowers patients to actively participate in their treatment journey, leading to increased satisfaction and improved self-perception.